(untitled) (Research, Society and Development, 2020)
The study aimed to address the importance of healthy eating with children in the early grades of a public school in the city of Dois Vizinhos-PR. The activity was initially carried out with the application of a questionnaire seeking to analyze the students’ prior knowledge and, afterwards, a lecture on food, exposing with the aid of the food pyramid the variety and quantity that should be ingested for each type of food. Soon after, educational videos were shown, and recreational activities were applied in order to promote the perception of the importance of consuming nutritious foods for a good quality of life. Through the results it was found that in general students understand the concept of healthy eating satisfactorily, however a portion of students does not reflect this perception in practice, with low fruit intake and high consumption of sweets. It is important to guide children to the practice of healthy eating, and playful activities can be a good instrument for addressing the topic with elementary school students.